KANDUNGAN FLAVONOID DAN KAPASITAS ANTIOKSIDAN TOTAL EKSTRAK ETANOL DAUN BINAHONG [Anredera cordifolia(Ten.)Steenis.] - Selawa, Widya; Runtuwene, Max R J; Citraningtyas, Gayatri (UNIVERSITAS SAM RATULANGI, 2013)
ABSTRACT The objectives of this research were to determineflavonoid content and total antioxidant capacity ofÂ Ethanolic extract of Binahong Leaf[Anredera cordifolia (Ten.) Steenis]. Total flavonoid were evaluated using Chang (2002) method, identification of flavonoid using thin layer chromatography and color reaction. Evaluation of antioxidant activity using ferric reducing antioxidant power (FRAP) method. The results shows that ethanolic extract of Binahong leaf possess total flavonoids 11,266 mg/kg (fresh) and 7,687 mg/kg (dry). Flavonoids contain in both extracts were flavonols group. Ethanolic extract of Binahong possess total antioxidant 4,25 mmol/100g (fresh) and 3,68 mmol/100g (dry). Keywords: total flavonoids, total antioxidant, ferric reducing antioxidant power,Anredera cordifolia Steenis.